Perceptions of Ambulatory Workflow Changes in an Academic Primary Care Setting. Issue 3 (July 2017) - Hanak, Michael A.; McDevitt, Colleen; Dunham, Daniel P.
Abstract : As health care moves to a value-based system, the need for team-based models of care becomes increasingly important to adequately address the growing number of clinical quality metrics required of health care providers. Finding ways to better engage certified medical assistants (CMAs) in the process allows providers to focus on more complex tasks while improving the efficiency of each office visit. Although the roles and responsibilities for CMAs across the specialties can vary widely, standardizing the work can be a helpful step in scaling best practices across an institution. This article presents the results of a survey that evaluated various components of a CMA workflow in adult primary care practices within an academic medical center. Although the survey identified improved engagement and satisfaction with standardized changes overall, it also showed time constraints and provider discretion forcing unplanned modifications. Reviewing and reconciling medications seemed to be the most challenging for CMA staff, leading us to reconsider their involvement in this aspect of each visit. It will be important to continue innovating and testing team-based care models to keep up with the demands of a quality-based health care system.